Pengembangan Bahan Ajar Biologi Berbentuk Leaflet Untuk Siswa Kelas X Sekolah Menengah Atas Negeri 3 Kerinci : (Development Of Leaflet Form Biology Teaching Materials Form Class X Student State High School 3 Kerinci) - Salahuddin, Salahuddin; Nofriadi, Nanang; Syahmi, Wahilman; Kurniawan, Ferry; Bunaya, Siti (BIODIK, 2024)
The teaching materials used during the teaching and learning process do not suit the students' character, for example the material is very dense, the size is very thick, the images displayed are black and white so this affects learning motivation. The aim of the research is to see the validity, practicality and effectiveness of teaching materials in the form of leaflets. This type of research is R&D (Research and Development) which uses the 4D model (Define, Design, Development and Disseminate). The subjects used in this research were expert lecturers, teachers and tenth grade students of SMAN 3 Kerinci. The research results show that the content/material expert validation test got a score of 86.1% with valid criteria, the design expert got a score of 82.2% with the valid category and the language expert got a score of 91.43% with very valid criteria. Analysis of the results of the practicality test of the teacher's assumptions obtained a score of 95.56% with the very practical category, then the results of evaluating the students' assumptions received scores of 90, 63% and 91.17 with very practical criteria. Analysis of test data on the effectiveness of assessing student activities obtained scores of 90.23% and 92.16% with very efficient criteria. From the research results, it can be concluded that the design of this leaflet teaching material is valid, very practical and very efficient to be applied in Biology learning for class X students at SMAN 3 Kerinci. Key words: Teaching Materials, Leaflets, Biology abstrak. Bahan ajar yang digunakan pada saat proses belajar mengajar tidak menyesuaian dengan karakter siswa misalkan materi yang sangat padat, ukuranya sangat tebal, gambar yang ditampilkan hitam putih sehingga hal ini berpengaruh terhadap motivasi belajar. Tujuan Penelitian adalah ingin melihat validitas, praktikalitas, efektifitas bahan ajar berbentuk leaflet. Jenis Penelitian ini ialah R&D ( Research and Development) yang memakai model 4D (Define, Design, Development and Disseminate). Subjek yang digunakan dalam riset ini ialah dosen pakar, guru serta siswa kelas sepuluh SMAN 3 Kerinci. Hasil riset menampilkan kalau uji validasi pakar isi/materi mendapatkan skor 86,1% dengan kriteria valid, pakar desain mendapatkan skor 82,2% dengan kategori valid serta pakar bahasa mendapatkan skor 91, 43% dengan kriteria sangat valid. Analisis hasil uji coba kepraktisan asumsi guru diperoelh skor sebesar 95, 56% dengan kategori sangat praktis kemudian hasil evaluasi asumsi siswa mendapatkan skor 90, 63% dan 91,17 dengan kriteria sangat praktis. Analisis data uji keefektifan penilaian aktifitas siswa memperoleh score 90,23 % dan 92,16 % dengan kriteria sangat efisien. Dari hasil riset bisa disimpulkan jika desain bahan ajar leaflet ini valid, sangat praktis serta sangat efisien untuk diterapkan dalam pembelajaran Biologi siswa kelas X SMAN 3 Kerinci. Kata kunci: Bahan Ajar, Leaflet, Biologi